1991
DOI: 10.1177/002221949102400807
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Adoptees Among Special Education Populations

Abstract: A statewide survey of public and private schools was conducted to determine the prevalence of adoptees among children classified for educational purposes as neurologically impaired (NI), perceptually impaired (PI), or emotionally disturbed (ED). Results indicated that adopted children were overrepresented in these special education populations, accounting for 6.7% of NI students, 5.4% of PI students, and 7.2% of ED students. Implications of the findings for educational and clinical intervention are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
7

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 28 publications
0
16
0
7
Order By: Relevance
“…Though adopted children are generally overrepresented in special education classes and show lowered general school adjustment (Brodzinsky & Steiger, 1991 ;Verhulst et al, 1990 ;Wierzbicki, 1993), some of our discrepant findings may be explained by differences in the age at placement (Tizard, 1991). In a Dutch study by Hoksbergen, Juffer, and Waardenburg (1987), a group of mostly infant-placed 9-year-old internationally adopted children were shown to have favorable school adjustment.…”
Section: Discussionmentioning
confidence: 66%
“…Though adopted children are generally overrepresented in special education classes and show lowered general school adjustment (Brodzinsky & Steiger, 1991 ;Verhulst et al, 1990 ;Wierzbicki, 1993), some of our discrepant findings may be explained by differences in the age at placement (Tizard, 1991). In a Dutch study by Hoksbergen, Juffer, and Waardenburg (1987), a group of mostly infant-placed 9-year-old internationally adopted children were shown to have favorable school adjustment.…”
Section: Discussionmentioning
confidence: 66%
“…adopted individuals are more likely than biological, non-adopted children to seek mental health services as adolescents and adults (e.g., Mech, 1973;Zill, 1985) and Brodzinsky and Steiger (1991) reported that adopted children tended to be overrepresented in special education populations. A meta-analysis emphasizing the psychological difficulties for children and families associated with adoption was written by Wierzbicki (1993).…”
mentioning
confidence: 99%
“…There is evidence that adopted children tend to show behavior problems and difficulty to cope with stress and depression Brodzinsky, 2002, 1994), there are also likely repercussions on the construction of close human relationships and social competence (Brodzinsky, et al 1984). Furthermore, there have been studies about the academic performance of adopted children which suggest that adopted children are overrepresented in school groups in need of support due to the presence of learning disabilities, attention deficit disorder and emotional imbalances (Silver, 1989;Deutsch et al, 1982 andSteiger, 1991).…”
Section: The Transformational Potential Of Higher Education Inclusionmentioning
confidence: 99%